Usnic Acid Isolated from Usnea antarctica (Du Rietz) Reduced In Vitro Angiogenesis in VEGF- and bFGF-Stimulated HUVECs and Ex Ovo in Quail Chorioallantoic Membrane (CAM) Assay - Klaudia Petrová; Miriam Bačkorová; Zuzana Demčišáková; Eva Petrovová; Michal Goga; Mária Vilková; Richard Frenák; Martin Bačkor; Ján Mojžiš; Martin Kello (Life, 2022)
Natural products include a diverse set of compounds of drug discovery that are currently being actively used to target tumor angiogenesis. In the present study, we evaluated the anti-angiogenic activities of secondary metabolite usnic acid isolated from Usena antarctica. We investigated the in vitro effects on proliferation, migration, and tube formation of VEGF- and bFGF-stimulated HUVECs. Ex ovo anti-angiogenic activity was evaluated using the CAM assay. Our findings demonstrated that usnic acid in the concentration of 33.57 µM inhibited VEGF (25 ng/mL) and bFGF (30 ng/mL)-induced HUVECs proliferation, migration, and tube formation. The ex ovo CAM model was used to confirm the results obtained from in vitro studies. VEGF- and bFGF-induced vessel formation was inhibited by usnic acid after 72 h in over 2-fold higher concentrations compared to in vitro. Subsequently, histological sections of affected chorioallantoic membranes were stained with hematoxylin–eosin and alcian blue to determine the number and diameter of vessels as well as the thickness of the individual CAM layers (ectoderm, mesoderm, endoderm). Usnic acid was able to suppress the formation of VEGF- and bFGF-induced vessels with a diameter of less than 100 μm, which was demonstrated by the reduction of mesoderm thickness as well.